Multiple perspectives of entrepreneurship : text, readings, and cases - Jennings, Daniel F. (South-Western, 1994)
This book is divided into four parts: Entrepreneurship and Economic Theory; Behavioral Aspects of Entrepreneurs; Corporate Entrepreneurship; and Cases.